A cultural perspective of organizational behavior in construction industry: an international viewpoint. (4th March 2017) - Akiner, Ilknur
ABSTRACT: The ability of the construction firms to successfully organize themselves internally and respond to the environment externally is related to their organization culture, an intangible force currently believed to play a tangible role in affecting the competitiveness, development and ultimate survival of the organizations. The main objective of this study is to analyze the organizational behavior and culture of construction project participants based on their cultural orientation within the contracting firms. A questionnaire survey was based on some specific indices of the organizational culture and was conducted with the participants within the contracting firms. Both qualitative and quantitative research approaches were used and the responses to the survey items were analyzed using factor analysis. The results revealed that significant differences exist in specific cultural traits, 'paternality-certainty', 'competitiveness-individuality', 'feminity', and 'informality' within the contracting firms.